Pengaruh Strategi Peer Lessons Terhadap Peningkatan Hasil Belajar Siswa Pada Mata Pelajaran Fiqih Kelas V Di Madrasah Ibtidaiyah Muhammadiyah 14 Sumurgayam Paciran - Husni, Hilal; Suharsono (Jurnal Mahasiswa Pendidikan, 2022)
In this study the authors used the method of observation, interviews, test questions and data analysis as answers to the formulation of the problem. There are two approaches to the problem in the research, namely the theoretical approach which is presented in the introduction, the theoretical basis, the results of the research analysis, and the conclusion. From the results of research based on the data collected, it can be concluded that: in fact there is an effect of peer lesson strategy and improving the quality of learning outcomes for fifth grade students of Madrasah Ibtidaiyah Muhammadiyah 14 Sumurgayam as evidenced by the results of data analysis with the calculation "r" = 0.462, when compared to " r" at a significant level of 5% = 0.153 "r" product moment is greater than the Table. Thus, 0.462 whose magnitude ranges from 0.400 – 0.599 means that the correlation between the X variable and the Y variable is classified as a moderate correlation.